PENGARUH KONTEN PENGETAHUAN OLAHRAGA DI YOUTUBE TERHADAP PERILAKU BELAJAR MAHASISWA PRODI PENDIDIKAN OLAHRAGA UNIVERSITAS QUALITY BERASTAGI - Aser Paul Nainggolan; Rizki Bastanta B Manalu; Mos Devan Tarigan (Universitas Quality, 2022)
YouTube is a form of video-based social media that contains various information including sports to support learning. YouTube is constantly developing with useful content that can be used by students as additional facilities for information on the world of sports. Moreover, students are more active in using social media because they can quickly obtain new information. So that the purpose of this study is to analyze the influence of sports content on YouTube on the learning behavior of students of the Sports Education Study Program, Quality Berastagi University. This research is a quantitative descriptive research. While the samples used were 69 students of the Sports Education Study Program at the Quality Berastagi University class of 2019-2021. Data were collected using a questionnaire tool. Analysis of the data used is the Pearson product moment correlation. The results showed that rcount (0.581) > rtable (0.2114), which means that there is a relationship between Sports Knowledge Content on YouTube and the learning behavior of Quality Berastagi University Sports Study Program students class 2019-2021 with a correlation value of 0.581. While the coefficient of determination (the value of the influence of Sports Knowledge Content on YouTube with student learning behavior) is 34.2%. So it can be concluded that there is an influence between sports content on YouTube on the behavior of students of the Sports Education Study Program at Quality Berastagi University.